Remote Sensing for Climate Change (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue captures the latest research advances regarding remote sensing technologies and their applications in climate change research. A total of 16 original research articles authored by 105 researchers are included in this Special Issue, presenting recent advances in remote sensing technologies and the application of remote sensing technologies to climate change modeling, monitoring, and impact assessment.